2022
DOI: 10.1161/atvbaha.122.318338
|View full text |Cite
|
Sign up to set email alerts
|

Arginase-1 Deletion in Erythrocytes Promotes Vascular Calcification via Enhanced GSNOR (S-Nitrosoglutathione Reductase) Expression and NO Signaling in Smooth Muscle Cells

Abstract: BACKGROUND: Erythrocytes (red blood cells) participate in the control of vascular NO bioavailability. The purpose of this study was to determine whether and how genetic deletion of ARG1 (arginase-1) affects vascular smooth muscle cell NO signaling, osteoblastic differentiation, and atherosclerotic lesion calcification. METHODS: Atherosclerosis-prone mice with conditional, erythrocyte-restricted deletion of ARG1 (apoE −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Experimental models have demonstrated that inhibiting or eliminating ARG1 can reinstate endothelial function by enhancing bioavailability 39 . Additionally, researchers have noted that ARG1 stimulates collagen synthesis in SMCs by channeling arginine metabolism toward proline, stimulating SMC proliferation, migration, and collagen deposition, thereby fostering vascular fibrosis and stiffness that ultimately underlie vascular occlusion 40 . In this context, the study corroborated elevated levels of both ARG1 and l ‐proline in the serum of AMN‐SARS‐CoV‐2 patients, suggesting the activation of the ARG1‐associated arginine metabolism and collagen synthesis pathways within the AMN‐SARS‐CoV‐2 milieu, suggesting ARG1 represents a promising therapeutic target for AMN‐SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models have demonstrated that inhibiting or eliminating ARG1 can reinstate endothelial function by enhancing bioavailability 39 . Additionally, researchers have noted that ARG1 stimulates collagen synthesis in SMCs by channeling arginine metabolism toward proline, stimulating SMC proliferation, migration, and collagen deposition, thereby fostering vascular fibrosis and stiffness that ultimately underlie vascular occlusion 40 . In this context, the study corroborated elevated levels of both ARG1 and l ‐proline in the serum of AMN‐SARS‐CoV‐2 patients, suggesting the activation of the ARG1‐associated arginine metabolism and collagen synthesis pathways within the AMN‐SARS‐CoV‐2 milieu, suggesting ARG1 represents a promising therapeutic target for AMN‐SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models have demonstrated that inhibiting or eliminating ARG1 can reinstate endothelial function by enhancing bioavailability [34]. Additionally, researchers have noted that ARG1 stimulates collagen synthesis in smooth muscle cells (SMCs) by channeling arginine metabolism toward proline, stimulating SMC proliferation, migration, and collagen deposition, thereby fostering vascular fibrosis and stiffness that ultimately underlie vascular occlusion [35]. In this context, the study corroborated elevated levels of both ARG1 and L-proline in the serum of AMN-SARS-CoV-2 patients, suggesting the activation of the ARG1-associated arginine metabolism and collagen synthesis pathways within the AMN-SARS-CoV-2 milieu, suggesting ARG1 represents a promising therapeutic target for AMN-SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…The above outcome is correspond with the conclusions of Tafuri et al [ 33 ]. The proximal segment is the most vulnerable to suffer the impact of blood flow velocity and fluid shear stress (FSS), and the vascular intima is damaged more easily, vascular smooth muscle cells are prone to differentiate into an osteoblast/chondrocyte phenotype, where inflammatory mediators, recruitment of activated macrophages, lipids and inflammatory factors are more likely to release and deposit [ 34 ]. The above factors are conducive to provoke and regulate the pathological process of plaque.…”
Section: Discussionmentioning
confidence: 99%